The Nature and Constituents of ‘Shukr’ and ‘Gratitude’ from the Perspective of the Qurʾān and Positive Psychology - Mohammad Mahdi Ajilian Mafogh; Seyyedeh Fatemeh Dastgheyb (آموزه‌های قرآنی)
In positive psychology, the significance of gratitude and its impact on individual and social well-being is a relatively emerging field of study. In the Qurʾān, however, divine discourse recurrently underscores the innumerable blessings bestowed upon humankind and calls upon individuals to acknowledge and express gratitude as a means of spiritual and personal growth. While shukr (Arabic: شکر, lit: thankfulness) is conceptualized as an ethical principle in the Qurʾān, gratitude in positive psychology is primarily examined in relation to social etiquette. This distinction necessitates a comparative study of the essence of these concepts in both domains. This research, employing a genealogical approach, investigates the structural composition and functional dynamics of shukr and gratitude within the Qurʾānic framework and positive psychology. The objective is to delineate the conceptual convergences and divergences between these two paradigms. Findings indicate that the Qurʾānic perspective on shukr integrates both foundationalist and functionalist dimensions, grounded in a self-constructed Qurʾānic epistemology. Conversely, positive psychology approaches gratitude from a purely functionalist standpoint, lacking a metaphysical or transcendental dimension. Moreover, despite superficial similarities, shukr in the Qurʾān and gratitude in positive psychology exhibit fundamental ontological and epistemological distinctions, each rooted in distinct intellectual traditions.